Omega-3 fatty acid supplementation decreases liver fat content in polycystic ovary syndrome: a randomized controlled trial employing proton magnetic resonance spectroscopy - Cussons, Andrea J; Watts, Gerald F; Mori, Trevor A; Stuckey, Bronwyn G A (The journal of clinical endocrinology and metabolism, 2009)
There is an association between nonalcoholic fatty liver disease (NAFLD) and the polycystic ovary syndrome (PCOS). Marine-derived omega-3 fatty acids have favorable effects on cardiovascular risk and could reduce liver fat in NAFLD. The primary aim of this study was to examine the effects of omega-3 fatty acids on liver fat in PCOS. The secondary aim was to assess their effects on traditional cardiovascular risk factors. We conducted a randomized, crossover study at a tertiary cardiovascular research center. Twenty-five women with PCOS (mean age, 32.7 yr; mean body mass index, 34.8 kg/m(2)) participated in the study. We compared 4g/d of omega-3 fatty acids with placebo over 8 wk. The primary outcome measure was hepatic fat content quantified using proton magnetic resonance spectroscopy. Secondary outcome measures included fasting lipids and blood pressure. Omega-3 fatty acids significantly decreased liver fat content compared with placebo [10.2 (1.1) vs. 8.4 (0.9)%; P = 0.022]. There was also a reduction in triglycerides [1.19 (1.03-1.47) vs. 1.02 (0.93-1.18) mmol/liter; P = 0.002], systolic blood pressure [124.1 (12.1) vs. 122.3 (14.5) mm Hg; P = 0.018], and diastolic blood pressure [73.2 (8.4) vs. 69.7 (8.3) mm Hg; P = 0.005] with omega-3 fatty acids compared with placebo. Omega-3 fatty acids particularly decreased hepatic fat in women with hepatic steatosis, defined as liver fat percentage greater than 5% [18.2 (11.1) vs. 14.8 (9.3)%; P = 0.03]. Omega-3 fatty acid supplementation has a beneficial effect on liver fat content and other cardiovascular risk factors in women with PCOS, including those with hepatic steatosis. Whether this translates into a reduction in cardiometabolic events warrants further study.